Living Donor Liver Transplant in patients with Hepatorenal Syndrome without the use of Intraoperative Renal Replacement Therapy, a single‐center experience. Issue 5 (9th March 2021) - Singh, Shweta A.; Prabhudesai, Aaditya Anil; Subramaniyan, Rajkumar; Madan, Kaushal; Yadav, Vivek; Pandey, Vijaykant; Nasa, Vaibhav; Goyal, Sumit; Das, Dibya Jyoti; Acharya, Rajgopal M.; Agarwal, Shaleen; Gupta, Subhash
Abstract: Background: Continuous Renal Replacement Therapy (CRRT) is often used to support the intraoperative course during liver transplantation (LT) for patients with HRS. However, the use of intraoperative CRRT (IOCRRT) is not without its problems. Living donor liver transplantation (LDLT) is a planned operation and is possible without IOCRRT as the recipient can be optimized. Aim: To study the peritransplant outcomes of patients with CLD and HRS undergoing LT without IOCRRT. Methods: Analysis of LT program database for perioperative outcomes in patients with HRS from Feb 2017 to Dec 2018. Results: 87/363 (23.9%) adult LDLT patients had HRS, of whom 31 (35.6%) did not respond (NR) to standard medical therapy (SMT) prior to LT. Modified perioperative protocol enabled the NR patients (who were sicker and in persistent renal failure) to undergo LT without IOCRRT. Postoperative renal dysfunction was similar (2 in NR and 2 in R) at 1 year. Post‐LT survival was also not different at one month (83.87% in NR and 87.5% in R [ p  = .640]) and at 1 year (77% in NR vs 80.4% in non‐responders [ p  = .709]). Conclusion: IOCRRT can be avoided in HRS patients undergoing LDLT without compromising their outcomes (post‐LT survival and RD), even in patients who have not responded to SMT, preoperatively.